An Analysis of The Causes of Premaritial Sex Among the youth In secondary schools : acase study of Mackay College Natateete in Rubaga Divison, kampala - Kabunga John . (Kampala : Uganda cahristian University Mukono, 2009)
Descriptive Cataloguing Uganda christio\an University BCDM
Includes Biblography (p.31)